ATTRIBUTES OF EFFECTIVE ECONOMICS EDUCATION INSTRUCTORS: A CASE STUDY AT THE ECONOMICS EDUCATION DEPARTMENT FISE-UNY - Purnastuti, Losina (International Business Education Journal, 2009)
The purpose of this study was to discover the attributes of economics instructors that are associated with teaching effectiveness using responses from students evaluations of teaching effectiveness (SETE) surveys at the Economic Education Department Social Sciences and Economics Faculty Yogyakarta State University. This study modifies and adopts L. F. Jameson Boex’s model that examines attributes of effective economics instructor at Georgia State University. This models defines six broad instructor attributes and estimates how each of these attributes to the effectiveness of economics instructors as perceived by students. To examine the attributes of economics instructors and how these attributes are associated with the effectiveness of instruction, I used data from student evaluations of teaching effectiveness (SETE) questionnaires for economics instructors at Economics Education Department Social Sciences and Economics Faculty Yogyakarta State University. In this study, I defined and quantified six instructor attributes. I define and qualified six composite instructor attributes. Subsequently, the effects of the six instructor attributes, as well as selected course, student, and instructor characteristics, on the teaching effectiveness ratings were determined using an ordered probit model.